Structural Features of InPbGaSnCu Molten High Entropy Alloy - S. I. Mudry; R. M. Bilyk; R. Ye. Ovsianyk; Yu. O. Kulyk; T. M. Mika (Фізика і хімія твердого тіла, 2020)
X-ray diffraction method has been carried out to study the structure in the equiatomic InPbGaSnCu highentropy alloy in liquid state. Structure factors and pair correlation functions have been analyzed and used todetermine the main structure parameters. Existence of shoulder on right hand side of principal peak and itstransformation was the main feature of structure factors. Comparison of structure functions and main parametersobtained from them for multicomponent alloy with ones for constituent elements shown that mixing process isrelated with formation of structural inhomogeneities in liquid state.